Zigzag spin structure in layered honeycomb Li3 Ni2 SbO6: a combined diffraction and antiferromagnetic resonance study - Kurbakov, Alexander I.; Park, Jaena; Koo, Changhyun; Klingeler, Rüdiger (Physical review, 2017)
The magnetic structure of Li3Ni2SbO6 has been determined by low-temperature neutron diffraction, and the crystal structure has been refined by a combination of synchrotron and neutron powder diffraction. The monoclinic (C2/m) symmetry, assigned previously to this pseudohexagonal layered structure, has been unambiguously proven by peak splitting in the synchrotron diffraction pattern. The structure is based on essentially hexagonal honeycomb-ordered Ni2SbO6 layers alternating with Li3 layers, all cations and anions being in an octahedral environment. The compound orders antiferromagnetically below TN=15K, with the magnetic supercell being a 2a×2b multiple of the crystal cell. The magnetic structure within the honeycomb layer consists of zigzag ferromagnetic spin chains coupled antiferromagnetically. The ordered magnetic moment amounts to 1.62(2)μB/Ni, which is slightly lower than the full theoretical value. Upon cooling below TN, the spins tilt from the c axis, with a maximum tilting angle of 15.6∘ at T=1.5K. Our data imply non-negligible ferromagnetic interactions between the honeycomb layers. The observed antiferromagnetic resonance modes are in agreement with the two-sublattice model derived from the neutron data. Orthorhombic anisotropy shows up in zero-field splitting of Δ=198±4 and 218±4GHz. Above TN, the electron spin resonance data imply short-range antiferromagnetic order up to about 80 K.